(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
This study focuses on the use of the Judiciary to question and force the Public Administration to develop public policies. The Social and Democratic Rule of Law is addressed, in which social rights must have immediate applicability, highlighting the rights-guaranteeing role of the Judiciary, which aims to protect the dignity of the human being and the axiological values incorporated into social models, which have democracy as an inalienable guarantee. The issue dealt with is of great importance, and the Constitution provides the answer to the extent and limits of the Judiciary’s control in this area of social rights. A clear and reasoned interpretative methodology must be used in order to remove any subjectivism, allowing for a critical analysis of the option taken, thus protecting the specific cases that require the protection of fundamental rights.